Validation of prognostic factors and survival of patients with multiple myeloma in a real-life autologous stem cell transplantation setting: a Swiss single centre experience (Swiss Medical Weekly, 2011)
PRINCIPLES: High-dose chemotherapy with subsequent autologous stem cell transplantation (ASCT) is an important treatment option in younger patients with multiple myeloma (MM). We analysed the outcome of patients treated at our institution outside the clinical trials framework and tried to identify risk factors prognostic for survival. METHODS: Medical histories of the patients were screened for response, event-free survival (EFS) and overall survival (OS). Pre-transplant variables were analysed to identify possible prognostic risk factors. RESULTS: Overall, 182 ASCT were performed in 120 patients with MM from 2002 to 2007. Treatment-related mortality (TRM) was 0.5%. Median EFS was 23.1 months (95% confidence interval [CI]: 19.4–28.4) and median OS was 49.8 months (95%CI: 43.7–not reached) in the whole patient population. The median OS in patients who received one ASCT was 46.4 months (95%CI: 35.2–not reached), and 63.7 months (95%CI: 48.9–not reached) in patients who underwent double ASCT. Patients who already achieved a complete remission (CR) before ASCT had a longer EFS (p = 0.016) than patients without CR. Additionally, patients who achieved a CR after ASCT had a longer EFS (p = 0.0061) and OS (p = 0.0024) than patients without CR. ISS stage